2000
DOI: 10.2307/2641296
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Mexico's Recent Land-Use Change: A Region's Contribution to the Global Carbon Cycle

Abstract: We applied modeled biomass density estimates to changes in land use/land cover (LU/LC) statistics for the intensively impacted and highly fragmented landscape of tropical Mexico to estimate the flux of carbon (C) between terrestrial ecosystems and the atmosphere between 1977 and 1992. Biomass densities were assigned to hybrid LU/LC classes on vegetation maps produced by Mexican governmental organizations and, by differencing areas and biomass C pools, net C flux was calculated in the eight-state tropical regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 48 publications
3
36
1
Order By: Relevance
“…Delaney et al (1997) reported 285 Mg ha -1 above ground biomass of Venezuela Tropical moist forest. The above ground biomass is very similar to Cairns et al (2000) for the semi-evergreen forest of Yucatan Peninsula (111.2 Mg ha -1 ), but less than the Veracruz (225.8 Mg ha -1 ). Brown et al (1995) and Golley et al (1975) Singh et al (2009).…”
Section: 779supporting
confidence: 49%
“…Delaney et al (1997) reported 285 Mg ha -1 above ground biomass of Venezuela Tropical moist forest. The above ground biomass is very similar to Cairns et al (2000) for the semi-evergreen forest of Yucatan Peninsula (111.2 Mg ha -1 ), but less than the Veracruz (225.8 Mg ha -1 ). Brown et al (1995) and Golley et al (1975) Singh et al (2009).…”
Section: 779supporting
confidence: 49%
“…This forest area is isolated from other lowland tropical forests by a broad belt ([130 km) of intensively used land dominated by pastures and cash crops. The ecological isolation of Los Tuxtlas forests on this scale has existed for at least 35 years [see maps in Cairns et al (2000)] but most likely since the 1950s, when extensive transformations of natural habitats to mostly cattle ranches began (Mendoza et al 2005). Localities B and C are in an area of larger forest remains beyond that belt of farmland, flanking the northeastern slopes of the central cordillera in western Veracruz/eastern Oaxaca.…”
Section: Fragmentation Studymentioning
confidence: 99%
“…1) in southern Mexico. Between 1977 and 1992 tropical Mexico experienced a reduction of about 28% of its total forest area, resulting in a highly disturbed landscape that includes cultivated land, secondary forest, grazing lands, and disturbed forests (Cairns et al 2000). Locality A is near the Biological Station ''Los Tuxtlas'', situated in the northeastern lowland part (18°30 0 N, 95°8 0 W) of the biosphere reserve Los Tuxtlas (Volcán San Martín) in the state of Veracruz.…”
Section: Fragmentation Studymentioning
confidence: 99%
“…Mexico's cloud forests are already fragmented, and researchers attribute a significant net release of carbon into the atmosphere to the conversion of both undisturbed and disturbed forest in Veracruz into open agricultural use (Cairns et al 2000). Here, the investment of individual smallholders in agroforestry and sustainable coffee farming could have a larger-scale positive impact on local and regional ecosystem functions (Pineda-López et al 2005).…”
Section: Discussionmentioning
confidence: 97%